Characterization of Pseudochloris wilhelmii potential for oil refinery wastewater remediation and valuable biomass cogeneration - Blažina, Maria; Fafanđel, Maja; Geček, Sunčana; Haberle, Ines; Klanjšček, Jasminka; Hrustić, Enis; Husinec, Lana; Žilić, Luka; Pritišanac, Ena; Klanjscek, Tin (Frontiers in Marine Science, 2022)
The microalgae of the genus Pseudochloris/Picochlorum are characterized by fast growth, and wide nutrient (type and concentration) and salinity tolerance, all contributing towards exploration of their use in high-density biomass production and wastewater bioremediation. In this study, removal of nitrogen and phosphorus nutrients from oil refinery wastewater was monitored during growth of the marine eukaryotic microalgae Pseudochloris wilhelmii, with emphasis on biochemical analyses of its biomass quality to evaluate suitability for biodiesel production. A series of growth experiments under various nutrient and light regimes were performed in a temperature range of 20-30°C to evaluate nutrient removal and biomass growth dependence on temperature. The highest removal rate of dissolved inorganic nitrogen reached under the given experimental conditions was 0.823 mmol/(gday) accompanied by the corresponding biomass productivity of 115.2 mg/(Lday). Depending on light and temperature, the final lipid concentration ranged 181.5 – 319.8 mg/L. Furthermore, increase in nutrient load decreased the maximum specific growth rate by 25%, and the maximum specific removal rate of the dissolved inorganic nitrogen by 19%, whereas the duration of bioremediation process was nearly doubled. In contrast, constant light exposure expedited the nitrogen removal, i.e. bioremediation process, by almost 40%, while supporting over three times higher biomass productivity and the highest maximum specific growth rate of 0.528 g/(gday). The conditions favoring the highest nitrogen removal and highest toxicity reduction in oil refinery wastewater are met at 24°C and 130 µmol phot/(m2s). The highest proportion of carbon-binding to the P. wilhelmii biomass was noticed under the same conditions, thus indicating them as the most favorable conditions for hydrocarbon removal as well as for CO2 sequestration. Pseudochloris wilhelmii therefore represents a promising candidate for oil refinery wastewater remediation and valuable biomass cogeneration on a large-scale.